Prevalence of musculoskeletal disorders among dentists: A pilot cross-sectional survey - Deepsikha Sahu; Shourya Tandon; Sonal Dhingra; B R Chinmaya; Sumanth Prasad; Esha Bali; Abhishek Ghosh (Wolters Kluwer Medknow Publications, 2015)
Introduction: Musculoskeletal symptoms are of major concern among dental practitioners. Work Related Musculoskeletal Disorders (WRMSD) has been reported to have a high prevalence among dentists in different parts of the world. Aim: To assess the prevalence of self-reported WRMSD among dental professionals in Gurgaon, one particular region of Delhi National Capital Region (NCR). Materials and Methods: A pilot cross-sectional survey of 250 dentists (response 81%) was done using a self-administered questionnaire, which consisted of 21 items based on the Nordic questionnaire for screening WRMSDs. Participants work related physical load characteristics, musculoskeletal symptom characteristics, etc., were evaluated. Results: A total of 206 dentists participated in the study, of which 106 were male, and 100 were female. The study yielded a prevalence of 81.06% (167 dentists) of which 79 males and 88 females were affected with MSD. There were 104 dentists who were young aged 20-29 years, 41 were 30-39 aged, 11 were above 40-49, and > 50 years suffered from MSDs. Around 59.2% young dentists aged 20-29 years, 24.2% were 30-39 years, 4.8% were 40-49 years, and 5.8% were above 50 years who were right handed, 2.9% dentists of 20-29 years age, 1.94% were 30-39 years, and 0.97% were 40-49 years who were left handed. Conclusion: This study found an overall prevalence rate of 81% among dentists with WRMSD in Delhi NCR. The measures for improving education and ergonomic evaluations are indicated on a large scale to prevent a decline in work performance and the incidence of WRMSDs among Delhi NCR dentists.